Sheehan’s syndrome: a case report - Khan, Shazia Ashraf; Lala, Prabha; Shullai, Wansalan; Singh, Abha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Sheehans syndrome or necrosis of pituitary gland is a rare complication of postpartum haemorrhage, initially described in 1937. Sheehans syndrome though rare is still one of the commonest causes of hypopituitarism in developing countries like ours. We present a case of young lady with this syndrome who presented with classical symptoms of hypopituitarism within 1 year of her delivery which was complicated by postpartum haemorrhage.